Loan Words in Bahasa Indonesia - Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2014)
Abstract The Indonesian has absorbed many loan words from other languages, including Sanskrit, Arabic, Dutch, Chinese, French, and English. Loan words in Bahasa Indonesia are in fact taken both from local language and foreign languages which then spelling, speech, and writing tailored to the narrative of the people of Indonesia to enrich vocabulary.  Based on the level of integration, loan words in bahasa Indonesia is divided into three parts.  First, loan words which are not necessarily undergo spelling change because they have been loan words for a long time, such as “radio” and “stereo’. Second, loan words whose spelling or pronunciation are adapted into Bahasa Indonesia spelling pattern. For examples, elektron, system and proton.  These loan words are used in Bahasa Indonesia context, but the pronunciation is still the same as the source. Third, the loan words whose pronunciation and spelling are already changed and adapted Indonesian spelling pattern. In this case the adaptation is minor that they are still recognized.  For examples, “persentase”, “ekonomi” and “politik”.Furthermore, lexical loans in Bahasa Indonesia can be in the form of pungutan dialect (dialect loans), pungutan mesra (well-absorbed loans), and pungutan kultural (cultural loans).  Pungutan dialect is a borrowing which is taken from one of the Indonesian dialects such as “brisik” or “bising” (noisy), “jejaka” or “bujangan” (bachelor) are adopted from Jakarta dialect.   Pungutan mesra  is a lexical borrowing which is adopted from another languages which exist in Indonesia such as “ganteng” (handsome), and “gawat” (dangerous) are adopted from Java. While, Pungutan kultural is any borrowing taken from any other languages which are not found in Indonesian.  The words such as “fakir” (poor), and “saham” (share) are taken from Arabic.  The words such as “panca-sila” (panca means five and sila means principles), and “tuna karya” (jobless) are taken from Sanskrit.  The words such as “arsip” (archive), “notabene” (notabene), “oli” (oil), and “vonis” (vonis) are adopted from Ducth.  Meanwhile, the words such as “approach” (approach), “audit” (audit, “bowling” (bowling), “gentlemen” (gentlemen), and “guest-house” (guest-house) are adapted from English. In addition, structural loan may cover all aspects of sounds and morphemes, or even sentence level.Loan words are adapted to fulfill the need for new words and new terms of  Bahasa Indonesia, as the consequence of the intensity of interaction in a modern society. It happens in technology, law, politics, economy and other fields such as religion, culture and social field. These loan words are used in Bahasa Indonesia because they have better connotation, shorter compared to its translation into Bahasa Indonesia, and the loan words had been chosen to make the agreement of meaning become easier since there are many synonym in Bahasa IndonesiaKey words: Loan words, adaptation, lexical loans